2019
DOI: 10.1177/0022057419864527
|View full text |Cite
|
Sign up to set email alerts
|

H2O-Centered Education: Helping Education Excellence Flow More Freely

Abstract: U.S. colleges and universities have been demonstrably ineffective at facilitating scholarship among their students. To become effective, psychological science suggests institutions must tap students’ intrinsic motivations and address their core values from Day 1 through graduation. This article describes a science-based, integrated set of solutions, labeled H2O-centered education, which creates and sustains instructional environments in which students develop and implement well-defined goals aligned with their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Callis and Osborn (2014) adopted an analytical approach to get the insights of the teachers who have taught abroad and have the global experience, which was limited to the context and did not mention anything on how it impacted education quality. Higley et al (2020) found that there is a need to tap students' intrinsic motivation and develop the concept of H2O centered JAMR 19,3 self-exploration environment. This can help students develop and implement goals, which are aligned with their motivations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Callis and Osborn (2014) adopted an analytical approach to get the insights of the teachers who have taught abroad and have the global experience, which was limited to the context and did not mention anything on how it impacted education quality. Higley et al (2020) found that there is a need to tap students' intrinsic motivation and develop the concept of H2O centered JAMR 19,3 self-exploration environment. This can help students develop and implement goals, which are aligned with their motivations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higley et al [15] found that the there is a need to tap student's intrinsic motivation and develop the concept of H 2 O-centred self-exploration environment. This can help students develop and implement goals, which are aligned with their motivations.…”
Section: Literature Reviewmentioning
confidence: 99%